Celebrity Endorsement, Brand Equity, and Green Cosmetics Purchase Intention Among Chinese Youth - Lili, Zhai; Al Mamun, Abdullah; Hayat, Naeem; Salamah, Anas A.; Yang, Qing; Ali, Mohd Helmi (Frontiers in Psychology, 2022)
The study examined the effect of celebrity attractiveness, celebrity trustworthiness, and celebrity cause fit on the attitude toward green cosmetics. This was followed by the effect of brand awareness, brand associations, brand loyalty, perceived quality, brand credibility on brand equity, including the impact of attitude toward green cosmetics and brand equity on the willingness to purchase green cosmetics among of young Chinese consumers. This study adopted a cross-sectional design and collected quantitative data from 301 respondents using a structured questionnaire, which was distributed online using various social media platforms. It was found that celebrity attractiveness, celebrity trustworthiness, and celebrity cause-fit had a significant impact on the attitudes toward green cosmetic, while brand loyalty, perceived quality, and brand credibility substantially affected brand equity. Moreover, the attitudes toward green cosmetics and brand equity had a strong impact on the willingness to purchase green cosmetics. To increase the sales for green cosmetics, the advertisements for it should have appeal, trustworthiness, and cause-fit celebrities to improve consumers’ attitudes and willingness to purchase green cosmetics. Finding of this study provide a guideline for green cosmetic manufacturers, to direct their resources to enhance brand loyalty, credibility, and perceived quality of the product they produce by highlighting the difference between conventional and green cosmetics.